2007
DOI: 10.1085/jgp.200609718
|View full text |Cite
|
Sign up to set email alerts
|

Subunit-specific Contribution of Pore-forming Domains to NMDA Receptor Channel Structure and Gating

Abstract: N-methyl-d-aspartate receptors (NMDARs) are ligand-gated ion channels that contribute to fundamental physiological processes such as learning and memory and, when dysfunctional, to pathophysiological conditions such as neurodegenerative diseases, stroke, and mental illness. NMDARs are obligate heteromultimers typically composed of NR1 and NR2 subunits with the different subunits underlying the functional versatility of NMDARs. To study the contribution of the different subunits to NMDAR channel structure and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
76
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(87 citation statements)
references
References 38 publications
10
76
0
1
Order By: Relevance
“…7A). An approximately similar pattern of state-dependent modification of the SYTANLAAF motif has also been demonstrated for NR1 and NR2C (Sobolevsky et al, 2002a(Sobolevsky et al, , 2007, and it seems that MTS modification of A7C in any subunit always lead to markedly enhanced constitutive opening of the channel (Beck et al, 1999;Jones et al, 2002;Yuan et al, 2005;Sobolevsky et al, 2007). However, the A7C mutations in NR1 and NR2A behave differently in response to partial glutamate site agonists (Jones et al, 2002).…”
Section: A651(nr2b) and A652(nr1) Of M3csupporting
confidence: 53%
See 1 more Smart Citation
“…7A). An approximately similar pattern of state-dependent modification of the SYTANLAAF motif has also been demonstrated for NR1 and NR2C (Sobolevsky et al, 2002a(Sobolevsky et al, , 2007, and it seems that MTS modification of A7C in any subunit always lead to markedly enhanced constitutive opening of the channel (Beck et al, 1999;Jones et al, 2002;Yuan et al, 2005;Sobolevsky et al, 2007). However, the A7C mutations in NR1 and NR2A behave differently in response to partial glutamate site agonists (Jones et al, 2002).…”
Section: A651(nr2b) and A652(nr1) Of M3csupporting
confidence: 53%
“…The A-to-T mutation at position 8 of this motif (A8T mutation) in the ␦2 glutamate receptor results in constitutive opening of the channel and causes neurodegeneration in the lurcher mutant mouse (Zuo et al, 1997). The T648A (T3A) and A649C (A4C) mutations in NR1 also made constitutively open channels (Kashiwagi et al, 2002;Sobolevsky et al, 2007). The M3c domain also shows significant gating conformational changes and thus may play an essential role in activation-deactivation gating of the receptor (Sobolevsky et al, 1999;Kohda et al, 2000;Jones et al, 2002;Kashiwagi et al, 2002;Low et al, 2003;Yuan et al, 2005) (but see Beck et al, 1999;Sobolevsky et al, 2002aSobolevsky et al, ,b, 2007.…”
Section: Introductionmentioning
confidence: 99%
“…The greater outward movement of the GluN2 M3 helices resulted in a rhombus shape for the positions of four homologous M3 residues, with the GluN1 residues at the obtuse-angle vertices and the GluN2 residues at the acute-angle vertices. This finding is supported by electrophysiological studies that showed unequal contributions of GluN1 and GluN2 subunits to channel gating (32). In the open state, substituted cysteines in the GluN1 M3 helices overall exhibited higher modification rates by methanethiosulfonate (MTS) reagents (consistent with the greater solvent exposure due to the positioning at the obtuse-angle vertices) than those in the GluN2 M3 helices.…”
Section: Introductionmentioning
confidence: 66%
“…The changes we observed in glutamate EC 50 among mutants at F636 most likely stem from modifications in channel gating because F636 is within the M3 domain at a considerable distance from the agonist binding site (Buck et al, 2000;Sobolevsky et al, 2007Sobolevsky et al, , 2009) and because of the role of the M3 segment in NMDA receptor ion channel gating (Jones et al, 2002;Sobolevsky et al, 2002b;Low et al, 2003;Yuan et al, 2005). However, the explanation for the changes in affinity is not clear and may differ among mutants at this position.…”
Section: Discussionmentioning
confidence: 83%